Pengolahan Air Gambut Dengan Biji Asam Jawa (Tamarindus Indica L) Sebagai Biokoagulan - Vina Lestari Riyandini; Shinta Elystia; Edward Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Peat water is surface water has a special characteristic, which is lightly browned, pH acidic and contains high organic and do not meet the quality standards of clean water that is PERMENKES No. 416/Menkes /Per/IX/ 1990 and Government Regulation No. 82 of 2001. One of the processing methods are widely applied in water treatment peat ie coagulation-flocculation. The use of natural coagulants such as tamarind seeds can be used as a substitute for synthetic coagulant. The aim of this study was to determine the influence of the mass and the particle size of tamarind seeds as coagulant for organic matter and COD, variations in the mass of peat water with tamarind seeds of 0.0025, 0.005, 0.0075, 0.01 and 0.0125 g / m3 and variations in particle size of 100, 170 and 200 mesh. Rapid stirring speed of 100 rpm for 4 minutes and stirring slow 40 rpm for 12 minutes. The results showed maximum efficiency on a mass of 2.5 g with 200 mesh tamarind seeds can decrease up to organic matter 76%, and COD 90%,. ANOVA test with SPSS shows that the mass of tamarind seeds and tamarind seeds particle size influence on organic matter and COD so that tamarind seeds can be used as a natural biokoagulan. Keywords: Water Peat, Tamarind Seed, Coagulation Flocculation